Patients' knowledge and attitudes regarding the prevention of diabetes mellitus complications at the internal medicine polyclinic - Zikran Zikran; Lisa Rizky Amalia; Muthmainnah Muthmainnah (Politeknik Negeri Subang, 2026)
Background: Diabetes mellitus (DM) is a chronic disease that requires effective management to maintain the patient's quality of life. Preventing DM complications necessitates adequate knowledge and a positive attitude, thereby helping patients avoid the complications associated with the disease. Purpose: This study aims to determine the relationship between patients' knowledge and attitudes and efforts to prevent diabetes mellitus (DM) complications at the Internal Medicine Outpatient Clinic of Raden Mattaher Regional General Hospital (RGH), Jambi. Method: This study employed an analytical survey method with a cross-sectional approach. The study population consisted of patients with diabetes mellitus, with a sample size of 84 respondents. Data collection was conducted using a questionnaire, and statistical analysis was performed using the Chi-square test at a 95% confidence level (0.05). Result: The study found a significant relationship between knowledge and the prevention of diabetes mellitus complications (p-value = 0.000). Attitude also showed a significant relationship with the prevention of diabetes mellitus complications (p-value = 0.000). Conclusion: Adequate knowledge and positive attitudes will enable patients to effectively engage in efforts to prevent diabetes complications; given that diabetes is a chronic disease capable of causing complications affecting all bodily organs, prevention is essential. Future researchers are encouraged to further explore knowledge and attitudes regarding the prevention of diabetes complications, and healthcare providers should assist in improving patient knowledge and attitudes to prevent complications associated with the disease.